Pengaruh Beban Kerja, Kompetensi, dan Penempatan Kerja Terhadap Kinerja PPPK sebagai Variabel Intervening - John Friadi; Bambang Satriawan; Nolla Puspita Dewi Dewi (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study aims to investigate the influence of workload, competence, and job placement on employee performance. In addition, work motivation is considered as a mediating variable in this influence.Methodology: This study uses a quantitative method with 291 respondents from PPPK in the Regional Government Organization of Karimun Regency. Data were collected through questionnaires and analyzed using SMARTPLS software to test the structural model.Results: Workload has no significant effect on performance, directly or through work motivation. Competence, job placement, and work motivation positively and significantly affect performance. Performance is influenced by these factors by 79.8%, with 20.2% from other variables. Work motivation is influenced by these factors by 61.8%, with 38.2% explained by other variables.Conclusions: Competence, job placement, and work motivation significantly impact PPPK performance. Workload has a negative but insignificant effect. Improving competence, proper placement, and motivation policies should be strengthenedLimitations: This study only involved PPPK in Karimun Regency, limiting generalization to other areas. Other variables affecting work performance and motivation (20.2% and 38.2%) were not studied.Contribution: This study provides insight into the factors that influence employee performance in Karimun Regency, with work motivation as a mediating variable between competence, placement, and performance.Keywords: Beban Kerja, Kinerja, Kompetensi, Motivasi, Penempatan KerjaHow to Cite: Sirait, M, Y, Satriawan, B, Dewi, N, P. (2025). Pengaruh Beban Kerja, Kompetensi, dan Penempatan Kerja Terhadap Kinerja PPPK sebagai Variabel Intervening. Studi Ilmu Manajemen dan Organisasi. 6(1), 39-52.